2005
DOI: 10.1103/physrevb.71.176501
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Localized behavior near the Zn impurity inYBa2Cu4O8as measured by nuclear quadrupole resonance”

Abstract: Williams and Krämer [Phys. Rev. B 64, 104506 (2001)] have recently argued against the existence of staggered magnetic moments residing on several lattice sites around Zn impurities in YBCO superconductors. This claim, which is in line with an earlier publication by Williams, Tallon and Dupree [Phys. Rev. B 61, 4319 (2000)], is however in contradiction with a large body of experimental data from different NMR groups. On the contrary, the authors argue in favor of a very localized spin and charge density on Cu s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 21 publications
(59 reference statements)
3
21
1
Order By: Relevance
“…Low temperature M-H curves of Zn doped YBCO single crystals showed 18 anomalous increase in magnetization and anisotropy. The NMR and MSR techniques also showed 19,20 that Zn doping causes magnetic modifications by inducing local magnetic moment on its neighbours in YBCO (123). Thus, we can also say that magnetic pair breaking is also very important for suppression of superconductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature M-H curves of Zn doped YBCO single crystals showed 18 anomalous increase in magnetization and anisotropy. The NMR and MSR techniques also showed 19,20 that Zn doping causes magnetic modifications by inducing local magnetic moment on its neighbours in YBCO (123). Thus, we can also say that magnetic pair breaking is also very important for suppression of superconductivity.…”
Section: Resultsmentioning
confidence: 99%
“…Low temperature M-H curves measured by them using SQUID also show a strong and anomalous increase in magnetization and an increase in anisotropy in the single crystals of the Zn-doped YBCO system [56]. Various other experimental techniques like Cu NMR, Y NMR, SQUID and Muon Spin resonance [21,[57][58][59][60] also show that the Zn doping causes magnetic modifications by inducing a local magnetic moment on its neighbours in the YBCO system. Apart from these, there are recent reports that the Al in LSCO [61], Mn in MgB 2 [17], Ho in Y 1−x Ho x Ni 2 B 2 C [18] also induce such local magnetic moments and enhance the Abrikosov-Gor'kov pair breaking [16].…”
Section: Discussionmentioning
confidence: 97%
“…This ignores the experimental data that show a strong correlation between the hole concentration and the Cu NQR frequency [13][14][15][16]. We do not believe that the results from Cu NQR measurements on a antiferromagnetic La 2 CuO 4 sample doped with Zn [18] proves that our use of the experimental correlation between the Cu NQR frequency and hole concentration is invalid as suggested by Julien et al [1]. This correlation is supported by a recent theoretical study that showed that the Cu electric field gradient is dominated by large positive and negative effects arising from the Cu 3d orbitals and virtual hoping from the neighboring oxygen ions to the unoccupied Cu 4d orbitals [17].…”
Section: Introductionmentioning
confidence: 83%
“…Julien et al [1] have criticized two of our publications reporting the results from NMR and NQR measurements on YBa 2 (Cu 1-x Zn x ) 4 O 8 [2,3]. These papers were published more that two and a half years ago and it should be accepted that the interpretation of data may change when new data or models are presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation